And Then There Is This Thing Called the Curriculum: Organization, Imagination, and Mind. (March 2016) - Ladson-Billings, Gloria
Despite the long history of curriculum studies in the American Educational Research Association, few past presidents have used their presidential addresses to speak about the curriculum and its importance in education research and teaching. In this essay, I examined the presidential addresses (and paper) of three well-known curriculum theorists—Harold Rugg, Maxine Greene, and Eliot Eisner—to share their perspectives on the curriculum as a vehicle for public discourse and democratic engagement. The essay ends with a challenge to AERA members to continue to use the study of curriculum as a vehicle for democracy, civic participation, and a more equitable and just society.